2015
DOI: 10.1016/j.vaccine.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of vaccination on the prevalence of gonorrhea

Abstract: Gonorrhea, one of the most common sexually transmitted infections worldwide, can lead to serious sequelae, including infertility and increased HIV transmission. Recently, untreatable, multidrug-resistant Neisseria gonorrhoeae strains have been reported. In the absence of new antibiotics, and given the speed with which resistance has emerged to all previously used antibiotics, development of a vaccine would be the ideal solution to this public health emergency. Understanding the desired characteristics, target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 43 publications
3
68
1
Order By: Relevance
“…243 We used our realistic dynamic power-law network model to investigate the impact of a range of 244 interventions against gonorrhoea, including increased condom use, more frequent screening and 245 immunisation. Our results confirm that vaccination shows great potential to reduce the burden of 246 gonorrhoea [49]: if a random 20% of individuals were immune, then the probability of outbreaks 247 persisting at least a year would be reduced by 16% with the outbreak size reduced on average by 31%. 248 (Fig 6).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…243 We used our realistic dynamic power-law network model to investigate the impact of a range of 244 interventions against gonorrhoea, including increased condom use, more frequent screening and 245 immunisation. Our results confirm that vaccination shows great potential to reduce the burden of 246 gonorrhoea [49]: if a random 20% of individuals were immune, then the probability of outbreaks 247 persisting at least a year would be reduced by 16% with the outbreak size reduced on average by 31%. 248 (Fig 6).…”
supporting
confidence: 68%
“…Furthermore, transmission of infection occurs only once the 47 network has been generated, with all partnerships being in place constantly from the beginning of the 48 simulation of infection transmission until the end. 49 An alternative method of producing static networks with a power-law degree distribution has been 50 proposed based on each network node having an intrinsic fitness parameter, and a function that 51 determines the probability that a network connection exists between any two nodes depending on 52 their fitness [17,18]. In a sexual network, this can be thought of as each individual having an inherent 53 propensity to seek new partnerships, with the probability of occurrence of each possible partnership 54 depending on the mutual attraction of two individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with our findings, they concluded that a vaccine of moderate level and duration of protection (60%, 10 years) could substantially reduce prevalence of infection by about 40%. 11 Our analysis is novel in considering the effect of a vaccination on the scale of all MSM within a country, by comparing realistic deployment strategies, and by incorporating the possible global emergence of a new extensively resistant strain, as well as incorporating a statistically rigorous analysis of incidence data.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 The rising antimicrobial resistance context raises the question of how best to deploy vaccines to decrease the overall burden of disease. [11][12][13] In 2016, the WHO announced a global health sector strategy on sexually transmitted infections, with a target of 90% reduction in gonorrhoea incidence by 2030. 14 15 Using a stochastic model of gonorrhoea epidemiology calibrated to recent incidence data, with varying future levels of antibiotic resistance, we investigated how protective and long-lasting a vaccine would need to be to reduce total incidence below the WHO target.…”
Section: Introductionmentioning
confidence: 99%
“…The models presented to the workshop suggested that a hypothetical gonococcal vaccine with partial efficacy could have a significant impact on disease prevalence, as long as coverage is high and protection lasts through the period of highest risk of disease among young people (36). There are currently insufficient data on the cost of disease, of its sequelae, or of prospective implementation strategies to provide a realistic appraisal of the potential costeffectiveness of GC vaccination.…”
Section: Session 2: Human Disease Modeling To Evaluate the Impact Of mentioning
confidence: 99%